Cryostratigraphy and the Sublimation Unconformity in Permafrost from an Ultraxerous Environment, University Valley, McMurdo Dry Valleys of Antarctica. (29th May 2017) - Lapalme, Caitlin M.; Lacelle, Denis; Pollard, Wayne; Fortier, Daniel; Davila, Alfonso; McKay, Christopher P.
Abstract: The cryostratigraphy of permafrost in ultraxerous environments is poorly known. In this study, icy permafrost cores from University Valley (McMurdo Dry Valleys, Antarctica) were analysed for sediment properties, ground‐ice content, types and distribution of cryostructures, and presence of unconformities. No active layer exists in the valley, but the ice table, a sublimation unconformity, ranges from 0 to 60 cm depth. The sediments are characterised as a medium sand, which classifies them as low to non‐frost susceptible. Computed tomography (CT) scan images of the icy permafrost cores revealed composite cryostructures that included the structureless, porous visible, suspended and crustal types. These cryostructures were observed irrespective of ground‐ice origin (vapour deposited and freezing of snow meltwater), suggesting that the type and distribution of cryostructures could not be used as a proxy to infer the mode of emplacement of ground ice. Volumetric ice content derived from the CT scan images underestimated measured volumetric ice content, but approached measured excess ice content. A palaeo‐sublimation unconformity could not be detected from a change in cryostructures, but could be inferred from an increase in ice content at the maximum predicted ice table depth. This study highlights some of the unique ground‐ice processes and cryostructures in ultraxerous environments. Copyright © 2017 John Wiley & Sons, Ltd.